Aromatic carbon from low-temperature biochar enhances bacterial phosphorus solubilization under saline-alkaline stress - Ziyi Ge; Shiyun Gan; Jiayi Li; Ziyue Xu; Siyu Wang; Xu Su; Yixuan Chen; Li Lin; Song Gao; Jun Meng (Bioresource Technology, 2027)

Whole genome sequencing analysis and functional characterization of Lacticaseibacillus rhamnosus HP-B1083 - Da-Hu Zhang; Zhen-Dong Tian; Bao-Zhi Ge; Qian-Meng Qi; Jia-Lin Lv; Hang Wu; Shao-Yang Hou; Shu-Hang Zhang (Brazilian Journal of Microbiology, 2026)

Degradation of mycotoxins in cow milk by dielectric barrier discharge cold plasma and its effect on milk quality - Yike Han; Shangchen Fu; Meng Li; Siqi Wang; Yijie Lu; Wupeng Ge; Chunfeng Guo; Yuan Zhou; Zhenpeng Gao (International Dairy Journal, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Elevated contaminations and risks of novel organophosphate esters and their transformation products in paddy soils - Zixiao Zhao; Meng Gao; Mohan Ma; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; Hongwen Sun (Journal of Environmental Sciences, 2026)

Long-term particulate matter exposure and coronary inflammation: A large-scale cohort study assessed by pericoronary fat attenuation index - Yuan Xu; Yi Zhang; Ge Guo; Xin Meng; Jing Wei; Yuanyuan Fan; Jiageng Cai; Cencen Wu; Zhulan Cai; Penghui Zhao; Yuwen Ruan; Zhaowei Yin; et al. (Environmental Pollution, 2026)

Targeted inhibition of JAK2 phosphorylation by GenX disrupts the JAK2-STAT3 pathway and induces cardiovascular toxicity in zebrafish: Insights from network toxicology and molecular dynamics - Yuzhi Zhao; Xiaoqiang Ge; Gaoyuan Wang; Qiaoling Zhang; Chengyu Geng; Zhongxiu Deng; Siyu Chen; Siyue Tan; Yifan Shi; Meng Zhao; Xinyi Wu; Shou-Lin Wang; et al. (Toxicology and Applied Pharmacology, 2026)

Influential factors on cyclic resistance of non-plastic and low-plastic silts - Min-Chien Chu; Meng-Heng Chiang; Huan-Yu Chou; Yu-Syuan Jhuo; Louis Ge; Chi-Chin Tsai (Soil Dynamics and Earthquake Engineering, 2026)

Energy-optimized thrust-space DWA for UUV path planning in ocean currents - Meng You; Zhanfeng Ying; Hao Ge; Dingcheng Peng; Xugang Wang (Ocean Engineering, 2026)

A vertical FVC profile retrieval method (OLV-FVC) based on airborne LiDAR point cloud under the constraint of optical remote sensing for forest plots - Hui Zhang; Wenquan Zhu; Ge Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Regional patterns and drivers of 15N fertilizer fate across China’s wheat systems: Integrating meta-analysis and machine learning - Yan’ge Yan; Shuiqin Zhang; Yingqiang Zhang; Meng Xu; Jiukai Xu; Yanting Li; Bingqiang Zhao; Liang Yuan (Field Crops Research, 2026)

3D solid-liquid heterogeneous anode/electrolyte interlayer for Zn anode: The trade-off between spatial regulation and ion transport kinetics - Haifeng Bian; Yilun Ren; Shunshun Jia; Qing Zhou; Ge Xue; Qimeng Wang; Haoran Wang; Jian Gu; Yujie Ma; Xiangkang Meng (Chemical Engineering Journal, 2026)

Precisely regulating the microenvironment towards robust active site for antibiotics degradation via Fenton-like reaction - Jiahao Cui; Wei Jian; Di Meng; Kun Wang; Jiaran Yao; Lina Li; Zijian Xu; Rile Ge; Junhu Wang; Jikun Li; Wonyong Choi; Yubao Zhao (Water Research, 2026)

Ni regulated LaMnO3 for selective nitrite to ammonia electroreduction - Kun Lang; Yuanyingxue Gao; Panzhe Qiao; Xudong Xiao; Mingyang Liu; Bin Wang; Xinrui Li; Wei Wu; Jingping Ge; Huiyuan Meng; Baojiang Jiang (Journal of Hazardous Materials, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Seasonal distribution and estuarine behavior of dissolved trace metals (Fe, Ni, Cu, Cd and Pb) across the Changjiang Estuary - Qiuya Gao; Zihui Hong; Yuncong Ge; Zhu Zhu; Meng Zhou; Shouye Yang; Ruifeng Zhang (Marine Chemistry, 2026)

MgO-modified PtSn/Ce-DMSN as an efficient catalyst for oxidative dehydrogenation of propane with carbon dioxide - Chao Peng; Jiang Li; Han-Qing Ge; Meng Yan; Zhong-Wen Liu (Chemical Engineering Journal, 2026)

Climate-adaptive performance and energy-saving potential of thermochromic façade materials across China climatic zones - Chenxi Hu; Fudan Liu; Liming Ge; Zehua Zhang; Xi Meng (Building and Environment, 2026)

Intelligent Vessels Localization Based on Adaptive Correlation Information Filter Network in Complex Marine and Port Environments - Lei Yan; Wei Zeng; Zhixin Xia; Bo Meng; Junli Ge; Deming Kong (Journal of Marine Science and Engineering, 2026)
Accurate and robust localization is essential for intelligent vessels operating in complex marine and port environments. However, single-sensor localization is often affected by limited observation range, environmental occlusion, local interference, and sensor degradation. Although multi-sensor fusion can improve localization reliability, unknown cross-correlated measurement noise arising from shared disturbances, time synchronization errors, communication delays, and inconsistent fusion rates may degrade traditional information-filter-based fusion methods. To address this problem, this paper proposes an Adaptive Correlation Information Filter Network (ACIFNet) for multi-sensor fusion localization of intelligent vessels. ACIFNet preserves the recursive structure of the extended information filter and uses a Transformer-based network to learn adaptive information-domain fusion weights, thereby compensating for unknown inter-sensor correlations without explicitly estimating the full correlation covariance matrix. Experiments on constant-velocity, coordinated-turn (CV), and three-degree-of-freedom vessel motion models, together with a real-world restricted-waterway dataset, demonstrate that ACIFNet achieves higher localization accuracy and stability than Edge Incorporative Fusion (EIF)-inexact fusion, measurement fusion, and KalmanNet. In the CV and three-degree-of-freedom experiments, ACIFNet reduces the mean RMSE by 48.7%, 23.2%, and 26.1%, respectively, compared with KalmanNet. On the real-world dataset, ACIFNet achieves a mean position error of 9.90 m, an RMSE of 11.24 m, and a cross-track error of 8.72 m. These results show that ACIFNet effectively combines the interpretability of information filtering with the adaptive representation capability of neural networks for robust multi-sensor fusion localization under unknown cross-correlated measurement noises.

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Pronounced molecular helicity as a design handle to accelerate spin-flip dynamics in B,N-embedded multi-resonance emitters toward ultra-high-efficiency OLEDs - Linfeng Jiang; Chao Feng; Jian Wu; Meng Li; Ge Gao; Zhengyang Bin; Jingsong You (Science Bulletin, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Experimental and numerical study on the effects of preheat temperature and steam dilution rate on the laminar burning velocity of CH4/O2/H2O - Shun Meng; Chunyu Zhang; Xinbin Ge; Shun Bian; Yang Hua; Changfa Tao; Yejian Qian; Peiyong Ma; Chunmei Wang (Fuel, 2026)

Carbon material–driven multistep electron transfer for efficient degradation of electron-rich pollutants: Synergistic effect of free radical and nonradical mechanisms - Meiyun Feng; Jiqiang Jia; Wenming Pei; Lichao Tan; Fukai Tang; Baoliu Pan; Keke Xu; Xin Liu; Mingzhu Zhang; Meng Zhang; Feng Ge (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Clay membrane effects on solute transport through the aquitard of a leaky aquifer system - Xianmeng Meng; Ge Yan; Lintao Shen; Qu Wang; Maosheng Yin; Dengfeng Liu (Hydrogeology Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Association Between Lead Exposure and Anthropometric Indicators in School-aged Children: A Longitudinal Study - Xiangju Wu; Yang Zhou; Linhong Li; Jieying Gao; Rongchang Xiao; Qian Yang; Meng Wu; Siyan Ye; Chengpeng Cui; Peng Lin; Ruifeng Luo; Ge Yan; et al. (Biological Trace Element Research, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Dynamic recovery sequence optimization of subway-bus network with constrained reinforcement learning - Shan Liu; Zhenhao Meng; Rui Jiang; Zhengli Wang; Ya Zhang; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Sustainable graphene from biomass via flash Joule heating: An innovative approach for cement mechanical performance - Xiaolian Su; Linyue Ge; Shan Huang; Xinye Wang; Hao Xie; Yiqiang Liu; Li Yi; Lingqin Liu; Junguang Meng; Haining Meng (Biomass and Bioenergy, 2026)

Eutrophication Assessment and Principal Component Analysis of the Yinghu Lake in Shaanxi Province - Guanghuan Ge; Xiaojun Meng; Jing Chen (Water, Air, & Soil Pollution, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Hybrid DEM-FDM modeling of heavy-haul railway transition zone slope effects on ballast particle movement and dynamic track responses - Yuanjie Xiao; Yuqin Wang; Zehan Shen; Meng Wang; Gulnaz Kanwal; Yuang Ge; Weidong Wang; Zhiwu Yu (Transportation Geotechnics, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Magnetic powder enhanced aerobic granular sludge for treatment of antibiotic containing wastewater: A dual enhancement in structural stability and nitrogen removal - Zhencheng Ge; Jun Nan; Xuesong Ye; Zhiling Li; Yibo Zhang; Fangmin Wu; Meng Chen; Bohan Liu (Journal of Environmental Chemical Engineering, 2026)

Differential remediation of tetracycline vs. sulfamethoxazole-contaminated soils by ZVI/BC: Impacts on rice growth, soil properties, and key regulatory factors - Xu Su; Jie Han; Xuanming Wang; Siyu Wang; Yixuan Chen; Ziyi Ge; Jun Meng (Journal of Environmental Chemical Engineering, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Unraveling the microbiological mechanism of carbon and nitrogen fixation coupling in agricultural soils - Yun Fang; Haoxin Fan; Xiangtian Meng; Juan Wang; Chaorong Ge; Huaiying Yao (Applied Soil Ecology, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

LINC01996 suppresses non-small cell lung cancer proliferation and metastasis by orchestrating the miR-12115/CNRIP1/Ras signaling axis - Yi Zhang; Xiaojing Li; Shanshan Liu; Qian Xue; Peize Meng; Xiaolu Ge; Qingnan Zhao; Haitao Ma (Clinical & Experimental Metastasis, 2026)

Interfacial electron transfer facilitated the bioreduction of biochar-sorbed organic pollutants: Division-of-labor roles of electroactive structures - Jia Xing; Shaofeng Zhou; Meng Ge; Zhiqiang Sun; Shujie Cai; Yingying Li; Meiying Xu (Water Research, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Recombinant Escherichia coli displaying conserved dominant B-cell epitopes of porcine epidemic diarrhea virus (PEDV) spike protein confers protective immunity against PEDV - Shengmei Pang; Congrui Zhu; PHYU HNIN WAI; Ge Li; Peng Dai; Guowei Ding; Guoqiang Zhu; Meng Ge; Weiping Zhang; Qiangde Duan (Chemical Engineering Journal, 2026)

Dynamic role of polystyrene microplastics in fouling evolution and structure-performance relationships among floc characteristics, cake layer structure and filtration performance of pre-coagulated low-pressure membrane processes - Meng Chen; Jun Nan; Ziyao Wang; Langrun Song; Zhencheng Ge; Fengmin Li (Chemical Engineering Journal, 2026)

Operational strategy matters: How stepwise versus shock increases in COD/N ratio affect aerobic granular sludge stability and microbial community dynamics - Zhencheng Ge; Jun Nan; Zhiling Li; Xuesong Ye; Yibo Zhang; Fangmin Wu; Meng Chen; Bohan Liu (Journal of Environmental Chemical Engineering, 2026)

Constructing dual-resistant nanofiltration membranes with superior antifouling and chlorine tolerance through a synergistic modification approach - Fanduo Meng; Yong Wang; Shuai Gong; Feiyue Ge; Wenxin Yan; Xiaozhen Lu; Liping Qiu; Feihong Wang; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

From immunity to table quality: The dual role of oleic acid in Litopenaeus vannamei aquaculture - Ze-Yu Jin; Jin-Meng Cai; Ge Zhao; Wen-Jie Li; Hao Yu; Hong-Wei Zhang; Xiao-Wen Zhang (Food Chemistry, 2026)

Precision screening of Lactobacillus with potential anti-allergenic using dual cell model - Xiang-Ge Xin; Yue Meng; Zai-Chen Li; Jun Xi; Jun Meng; Chang-He Ding; Dong-Ge Zheng; Ling-Guang Du; Shu-Song Wang (Food Bioscience, 2026)

Smart, tumor-targeted, and responsive intracellular delivery engineering (STRIDE) nanoplatform: co-delivery of siGLI1 and cisplatin prodrug to overcome lung adenocarcinoma chemoresistance - Ge Chen; Mengyang Liu; Yanan Sun; Shifei Zhang; Qingyi Liu; Yuxiang Liang; Kexin Cong; Meng Yan; Zhigan Zhang; Jinjiang Deng; Zongyu Wang; Ziqiang Li; et al. (Chemical Engineering Journal, 2026)

Characteristics of Submicron Aerosols (PM1) in a Yangtze River Delta Megacity: Composition, Sources, and Light Absorption - Shiyue Yang; Haifeng Meng; Ning Zhang; Shijie Cui; Yuanjie Shan; Yu Huang; Yunlong Xu; Chongchong Zhang; Xinlei Ge; Mindong Chen; Junfeng Wang (Advances in Atmospheric Sciences, 2026)

An Indirect Foot-End Touchdown Detection Method for the Underwater Hexapod Robot - Zonglin Liu; Meng Wang; Tong Ge; Rui Miao; Gangtai Lu (Journal of Marine Science and Engineering, 2025)
The underwater hexapod robot has advantages such as lower energy consumption and reduced environmental interference compared to ROVs and AUVs. The foot-end contact detection with the seabed is the key technology for adapting to complex terrains. This paper focuses on the ‘Dragon Crab’ underwater hexapod robot developed by Shanghai Jiao Tong University and proposes an indirect detection method that does not require foot-end contact sensors. By establishing the kinematic and dynamic models of the robot’s legs, combined with multi-order polynomial trajectory planning to reduce non-contact force interference, the foot-contact determination condition is defined. Through simulation experiments and force analysis of the legs, the contact detection parameters are estimated. Then, single-leg contact tests are conducted to obtain joint motor torque variation curves and foot-end height variation curves through the kinematic model, verifying the proposed contact detection conditions and parameters. Finally, the method is applied to underwater obstacle-crossing experiments of the underwater hexapod robot using triangular and wave gait patterns. Experimental results show that the method can accurately identify the foot-end contact state and has high applicability in complex underwater terrains.

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Cross-shelf and along-shore transport of trace metals in shelf sediments of the East China Sea - Ge Meng; Xiting Liu; Kaidi Zhang; Fangjian Xu; Mingyu Zhang; Xin Chang; Yu Gu; Guang-Chao Zhuang (Progress in Oceanography, 2025)

Phytochemical characterization of low-caffeine and high-theobromine wild tea Camellia yungkiangensis var. yuanbaoshanica reveal its special compositions - Taolin Chen; Herao Wu; Junwu Luo; Zhiwen Ge; Hao Zuo; Xifu Wang; Xuemei Yang; Shimin Li; Yinping Liao; Jiajia Meng; Zheng Zhang; Meili Chen; et al. (Food Chemistry, 2025)

Synthetic phenolic antioxidants in paddy soils from central China: Contamination characteristics and risk prioritization analysis - Mohan Ma; Meng Gao; Zixiao Zhao; Siyuan Li; Yimeng Si; Liman Wei; Yiting Ge; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; et al. (Environmental Pollution, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Grass root microbiomes exhibit broader niche breadths but stronger phylogenetic clustering than forb root microbiomes in a temperate steppe - Ren Bai; An-Hui Ge; Meng Zhou; Wen-Hao Zhang; Wenming Bai (Plant and Soil, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Stigmasterol protects H9c2 cells from angiotensin-II induced hypertrophy by regulating apoptosis and autophagy - Mingming Chang; Jinjin Meng; Ge Liu; Chao Shi (Molecular & Cellular Toxicology, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

Role of PANoptosis in cancer: Molecular mechanisms and therapeutic opportunities - Wen-Qing Wang; Zi Zhou; Feng-Xin Ge; Mukaddas Tayir; Meng-Yuan Hao; Dong-Dong Wu (Apoptosis, 2025)

The Association of Cadmium Exposure and Anthropometrics in School-Age Children: A Longitudinal Study - Meng Wu; Linhong Li; Tianwenjing Huang; Jieying Gao; Peng Gan; Shudan Liu; Dan Wu; Siyan Ye; Chengpeng Cui; Longjie Li; Ge Yan; Qin Liu (Biological Trace Element Research, 2025)

Metabolic syndrome and risk of dementia and cognitive decline: a systematic review and meta-analysis of prospective cohort studies from 6,753,197 participants - Qi Wang; Luyi Zhang; Ruiqi Xu; Kexin Meng; Lutong Pan; Xiaoyu Zhang; Long Ge; Dongshan Zhu (GeroScience, 2025)

Steinernema carpocapsae as a promising biological control agent against Spodoptera frugiperda pupae - Geng Meng Chen; Aleena Alam; Chen Ge; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Qiyun Li; Rizhao Chen (Crop Protection, 2025)

The role of aging biomarkers and reproductive hormones in the association between microcystin-LR exposure and semen quality - Kangfeng Ge; Jian Hou; Wenqian Huo; Xiao Liang; Jun Yang; Haibin Guo; Xingde Du; Ruiyang Meng; Feiyang Guo; Xin Wang; Yingfei Yang; Xiaodong Liu; et al. (Journal of Hazardous Materials, 2025)

Implementation of three-dimensional numerical manifold method for initiation and propagation simulation of brittle materials - Ge Kang; Liu chen Shu; Qiu meng Ouyang; Zheng Yang; You-jun Ning; Peng-wan Chen (International Journal of Rock Mechanics and Mining Sciences, 2025)

Association of ambient fine particulate matter (PM2.5) and its constituents with risk of pulmonary nodules in a lung cancer screening project - Xinyuan Ge; Ci Song; Chen Zhu; Yang Ding; Maojie Liu; Juan Yang; Chan Tian; Jiahao Zhang; Lili Wu; Lingying Zhu; Lei Shi; Xiangdong Cheng; et al. (Environmental Research, 2025)

Ecological Suitability Assessment of Larimichthys crocea in Coastal Waters of the East China Sea and Yellow Sea Based on MaxEnt Modeling - Shuwen Yu; Wei Meng; Hongliang Zhang; Hui Ge; Lei Wu; Yao Qu; Qiuhong Zhang; Yongdong Zhou (Journal of Marine Science and Engineering, 2025)
The Larimichthys crocea represents a critically important economic marine species in China’s East Yellow Sea. However, its populations have experienced significant decline due to overexploitation. Despite implemented conservation measures—including stock enhancement, spawning ground protection, and seasonal fishing moratoria—the recovery of yellow croaker resources remains markedly slow. To address this, our study employed the Maximum Entropy (MaxEnt) model to evaluate and characterize the habitat selection patterns of Larimichthys crocea, thereby providing a theoretical foundation for scientifically informed stock enhancement and resource recovery strategies. Species occurrence data were compiled from field surveys conducted during April and November (2019–2023), supplemented with records from the GBIF database and peer-reviewed literature. Concurrent environmental variables, including primary productivity, current velocity, depth, temperature, salinity, silicate, nitrate, phosphate, and pH, were obtained from the Copernicus and NOAA databases. After rigorous screening, 136 distribution points (April) and 369 points (November) were retained for analysis. The model performance was robust, with an AUC (Area Under the Curve) value of 0.935 for April (2019–2023) and 0.905 for November (2019–2023), indicating excellent predictive accuracy (AUC > 0.9). April (2019–2023): Nitrate, salinity, phosphate, and silicate were identified as the primary environmental factors influencing habitat suitability. November (2019–2023): Silicate, salinity, nitrate, and primary productivity emerged as the dominant drivers. Spatially, Larimichthys crocea exhibited high-density distributions in offshore regions of Zhejiang and Jiangsu, particularly near the Yangtze River estuary. Populations were also associated with island-reef systems, forming continuous distributions along Zhejiang’s offshore waters. In Jiangsu, aggregations were concentrated between Nantong and Yancheng. This study delineates habitat suitability zones for Larimichthys crocea, offering a scientific basis for optimizing stock enhancement programs, designing targeted conservation measures, and establishing marine protected areas. Our findings enable policymakers to develop sustainable fisheries management strategies, ensuring the long-term viability of this ecologically and economically vital species.

Depth matters: The impact of vegetation clipping on phosphorus fractions across peatland depth profiles - Yuchen Suo; Xin Guo; Leming Ge; Chenhao Cao; Meng Wang (Soil and Tillage Research, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Antibacterial effect of electrolysis combined with ZnO nanoparticles treatment on heterotrophic bacteria in simulated water - Ziyu Yan; Xuhui Wang; Dengjia Yuan; Min Xu; Junwei Wang; Honghua Ge; Xinjing Meng; Yuzeng Zhao (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

SiO2 nanofiber and graphene oxide assisted fabrication of silica aerogels with novel interpenetration networks for efficient oil adsorption and photothermal evaporation - Meng-Jie Chang; Ge Bai; Jun Liu; Qiu-Yu Hu; Shu-Yi Hu; Yan Yin; Shi-Shun Cao (Journal of Environmental Chemical Engineering, 2025)

Effect of MnFe2O4 loading on photocatalytic performance of BiVO4 for levofloxacin degradation with or without peroxydisulfate - Meng Tang; Liduan Zhang; Lijia Zheng; Ming Li; Ming Ge (Environmental Research, 2025)

MOF-encapsulated fullerene solid solutions: Harnessing maximal host-guest interactions for visible-light photocatalytic hydrogen generation - Zehu Wang; Haibing Meng; Xiaolong Liu; Ningning Wu; Libin Yang; Bo Wu; Gang Li; Qiwen Liu; Jie Li; Jiechao Ge; Chunru Wang (Chemical Engineering Journal, 2025)

Synergistic treatment of extracellular polymeric substances in Chlorella vulgaris recycled wastewater using Fenton oxidation coupled with granular activated carbon adsorption - Yufei Zhang; Xinyu Wen; Yanlin Zhang; Huihui Zhang; Menghan Chi; Yabin Zhao; Xiangyue Meng; Zhihong Tang; Daoyong Yu; Baosheng Ge (Bioresource Technology, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Machine Learning-Assisted Diagnosis of Abrupt Air Pollution Emissions: Insights From Firework Emissions in China - Lu Yang; Di Liu; Han Yang; Jie Fang; Qingxiao Meng; Yunjiang Zhang; Xinlei Ge (Aerosol Science and Engineering, 2025)

Paleoenvironmental changes in the northeastern margin of the Tibetan Plateau since MIS 3: Magnetic evidence from the second terrace of the Yellow River - Jiawen Zhao; Longsheng Wang; Yuzhu Zhang; Yinglu Chen; Shouyun Hu; Liwei Meng; Guiye Zhang; Yanju Ge; Chao Zhan; Qing Wang (CATENA, 2025)

Arctigenin inhibits high glucose-induced EMT and cell proliferation to alleviate benign prostatic hyperplasia companied with type 2 diabetes mellitus through MBOAT4/ acylated Ghrelin/GHS-R - Meng Gu; Jianchao Ge; Huan Xu; Yanbo Chen; Qi Chen; Zhong Wang; Bin Xu (Chemico-Biological Interactions, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Southward subduction of the Mongol–Okhotsk Ocean: constraints from Late Triassic granites in the Hailar Basin, NE China - Zhikun Dai; Zheng Ji; Qian Meng; Chuanbiao Wan; Wenjing Bai; Hao Yang; Junhui Bi; Wei Huang; Yongzhi Wang; Yu Dong; Wenchun Ge (International Geology Review, 2025)

Optimal Fluoride Concentration in Drinking Water for Preventing Dental Fluorosis and Caries in 8–12-Year-Old Children in Qingdao, China: A Restricted Cubic Spline and Spatial Epidemiological Analysis Following Rural Safe Drinking Water Interventions in Endemic Fluorosis Region - Xiaojuan Dou; Xiaoyi Liu; Shitao Liu; Changxun Ge; Shirui Yan; Di Wu; Xinyue Meng; Xinxiao Li; Junrui Pei; Fengying Ji (Biological Trace Element Research, 2025)

Deciphering the influence of heavy metals on adverse cardiovascular events using machine learning - Guanmou Li; Tong Zhang; Kunyang He; Miao Zhang; Jinlin Hu; Teng Ge; Meng Wang; Rongjun Zou; Xiaoping Fan (Toxicology Letters, 2025)

Fungal xylomannan as a dietary supplement: Activates hepatic AMPK/HIF1α signaling to attenuate insulin resistance - Yuhan Meng; Xiushi Jia; Lujuan Zheng; Min Wang; Jing Xia; Mingming Li; Junzhu Wei; Yanchen Qi; Chen Meng; Jiaxing Sheng; Pengyu Ge; Yuying Fan; et al. (Food Bioscience, 2025)

Study on the separation of nitric acid and acetic acid using multi-stage electrodialysis - Xiao Ge; Baole Li; Xiang Meng; Tiansheng He; Tianchi Li; Qi Yang; Zheng Wei; Taihong Yan; Zhongwei Yuan (Desalination, 2025)

A point-of-care SERS-based microdevice for multi-pesticide poisoning diagnostics towards first aid scenarios - Meng Jin; Hui Pan; Ge Gao; Mengping Zhang; Haiyan Wei; Xiao Meng; Wenwen Chen; Xinya Zhang; Ming Shang; Cuijuan Wang (Chemical Engineering Journal, 2025)

Reversible regulation of room temperature phosphorescence and fluorescence in cucurbit[8]uril-mediated lanthanide MOFs - Qingyu Niu; Zerong Ge; Xiao Liu; Tian-meng Guo; Zongjie Hu; Weihan Li; Zhiqiang Li (Chemical Engineering Journal, 2025)

Ultra-sensitive, versatile and portable detection of hydrazine in eco-environmental systems using a smartphone-integrated ratiometric fluorescent sensor - Xiao-Hong Li; Meng-Zhao Li; Xiao-Yan Yang; Tian-Yan Wang; Yin-Heng Luo; WMWW Kandegama; Jing-Yi Li; Ge-Fei Hao; Chun-Rong Liu (Journal of Hazardous Materials, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Characteristics of Wintertime Atmospheric PM1 in a Megacity in the Yangtze River Delta, China: A Comparative Study of 2015 and 2022 - Haifeng Meng; Yuanlong Huang; Shiyue Yang; Shijie Cui; Yangzhou Wu; Ning Zhang; Liangyu Feng; Xinlei Ge; Mindong Chen; Junfeng Wang; Eleonora Aruffoa (Aerosol Science and Engineering, 2025)

Breath of the chill: Transcriptomic exploration of respiration and energy metabolism in sweet potato roots during cold storage - Wanying Ge; Qian Zhou; Zhuohui Meng; Jihui Gao; Gang Chen; Yongxin Li; Huqing Yang (Postharvest Biology and Technology, 2025)

Effects of Clitocybe squamulosa polysaccharides on the intestinal microenvironment and microbiome of cyclophosphamide-induced mice - Xueran Geng; Dongdong Guo; Guangliang Ge; Zehui Li; Shuting Hou; Tergun Bau; Sitong Yao; Lijing Xu; Yanfen Cheng; Ludan Hou; Junlong Meng; Mingchang Chang (Food Bioscience, 2025)

Fusobacterium necrophorum mediates the inflammatory response in the interdigital skin and fibroblasts of dairy cows via the TNF-α/TNFR1/NF-κB pathway - Yang Yue; Anchi Zhang; Meng Liu; Yansong Ge; Enshuang Xu; Jiasan Zheng (Veterinary Microbiology, 2025)

Synthetic phenolic antioxidant contamination in farmland soils induced by mulching films: Distribution and transformation pathways - Shanxing Wu; Meng Gao; Bo Fang; Lili Rong; Zhanpeng Ge; Hao Chen; Yiming Yao; Yu Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Dietary emulsifier Polysorbate 80-induced lipotoxicity promotes intestinal senescence - Linlin He; Lan Zhang; Fanyi Meng; Jingge Wei; Fei Chen; Siqi Qin; Ge Jin; Hailong Cao (Food Research International, 2025)

Combination of NRPS/PKS tuning and morphological engineering enhanced iturin A production in Bacillus amyloliquefaciens - Zheng-Jie Hou; Hai-Meng Lai; Kai-Ge Song; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Enhanced production of lactic acid via glycerol selective oxidation over K-doped Pt/Sn-MFI catalysts - Haodong Xie; Haobin Wei; Zunlong Hu; Sida Ge; Yingshuo Guo; Pengfei Guo; Meng Wu; Xicheng Jia; Jiazhou Li; Tianliang Lu; Yuming Zhang; Wenhao Luo; et al. (Chemical Engineering Journal, 2025)

Genetic characterization of coronaviruses causing common cold symptoms based on micro-targeted capture sequencing - Qiao Qiao; Xiaojuan Zhu; Zixinrong Meng; Hongbin Zhang; Tao Wu; Kangchen Zhao; Yiyue Ge; Lunbiao Cui (Archives of Virology, 2025)

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Emulation of Schrödinger dynamics with metamaterials - Zhao-Xian Chen; Wan-Ge Song; Guang-Chen He; Xiao-Meng Zhang; Ze-Guo Chen; Haitan Xu; Emil Prodan (Science Bulletin, 2025)

CmERFIV-4-CmWRKY44-CmPSY1 modulates ethylene-induced β-carotene accumulation in oriental melon fruit - Fei Luo; Xiaoyu Duan; Ge Gao; Yaping Zhao; Meng Li; Hongyan Qi (Postharvest Biology and Technology, 2025)

Remediation effectiveness and mechanism on surfactant-enhanced remediation of low-permeability petroleum hydrocarbon contaminated soil under fracturing conditions - Shi-Jin Feng; Jiu-Ge Niu; Fu-Jiang Shi; Qi-Teng Zheng; Meng-Wen Gao (Journal of Hydrology, 2025)

Construction of ultra-light and flexible aerogels with superior high oil sorption capacity by controlling the mechanical property of SiO2 nanofibers - Meng-Jie Chang; Ge Bai; Jun Liu; Xin Li; Hui Wang; Shu-Yi Hu; Qiu-Yu Hu; Shi-Shun Cao; Jie Yang (Journal of Environmental Chemical Engineering, 2025)

Wearable triboelectric Ag/thermoplastic polyurethane yarns with core-shell structure for energy harvesting and underwater sensing - Suya Hu; Zhenya Ge; Meng Chen; Peng Ding; Wei Zhai; Guoqiang Zheng; Kun Dai; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2025)

Hollow and mesoporous nanospheres enable rapid ion migration on the zinc anode surface - Shunshun Jia; Haifeng Bian; Qing Zhou; Biao Wang; Ge Xue; Hao Wu; Fengqi Li; Zhonglu Hu; Yujie Ma; Jian Gu; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

A strategy to determine GRACE-FO kinematic orbit during the activation of flex power - Guanlong Meng; Haibo Ge; Tianhao Wu; Bofeng Li (GPS Solutions, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Alpha-Momorcharin, a type I ribosome inactivating protein, induced apoptosis of hepatocellular carcinoma SK-HEP-1 cells through mitochondrial pathway - Di Yang; Di Peng; Yiping Zhou; Zihao Qiang; Li Wan; Xiang Fan; Yanfa Meng; Ge Xu; Yao Meng (Natural Product Research, 2025)

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Procyanidins-Mediated Biological Denitrification Inhibition Reduces Fertilizer-Induced N2O Emissions in Acidic Tea Plantation Soils - Xing Han; Haiyang Yu; Miaoling Meng; Chaorong Ge; Ningguo Zheng; Huaiying Yao (Journal of Soil Science and Plant Nutrition, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Employing the spray system to improve the regional thermal environment in outdoor open space - Yi Gao; Liming Ge; Xi Meng (Urban Climate, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Aqueous phase photolysis of 4-nitrocatechol: Reaction kinetics, evolutions of chemical composition, light absorption and oxidation potential - Ruoyuan Lei; Yingying Sha; Haifeng Meng; Yu Huang; Jianhuai Ye; Dan Dan Huang; Yunjiang Zhang; Yun Wu; Yongjie Li; Xinlei Ge (Atmospheric Environment, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Antibacterial capacity and mechanism of the metabolites from two vaginal Lactobacillus strains - Jun Meng; Pan-Pan Dong; Xiang-Ge Xin; Yue Meng; Chang-He Ding; Jun Xi (Food Bioscience, 2025)

Visible light-activated Ti-MOF loaded metformin-hydrogel composite dressing for accelerated chronic diabetic wound healing - Meng Tian; Chuan Fan; Rujiao Ge; Guodong Liu; Lei Su; Haifeng Dong (Chemical Engineering Journal, 2025)

Co-effect of surface-preferred crystal plane and surface coating for stable zinc metal anodes - Qing Zhou; Haifeng Bian; Biao Wang; Shunshun Jia; Ge Xue; Hao Wu; Fengqi Li; Zhonglu Hu; Haijiao Xie; Yujie Ma; Jian Gu; Shaochun Tang; et al. (Chemical Engineering Journal, 2025)

Enhanced photocatalytic degradation of polycyclic aromatic hydrocarbons (PAHs) in biochar using nano-TiO2 under ultraviolet light irradiation: Effect and mechanisms - Ranran Wei; Yunyu Ge; Haibo Meng; Guangqun Huang; Jining Wu; Fengrui Wen; Huan Liu; Xiuli Shen (Chemical Engineering Journal, 2025)

Zero-strain high entropy spinel oxide (FeNiCuCrMn)3O4@rGO as high-performance anode for sodium ion battery - Bin Xiao; Xiaoyang Liu; Zelin Xie; Duyu Zheng; Juxing Zha; Jiqiu Qi; Fuxiang Wei; Qingkun Meng; Xiaolan Xue; Danyang Zhao; Yongzhi Li; Qing Yin; et al. (Chemical Engineering Journal, 2025)

Deciphering the key drivers of oxidative potential during ammonium nitrate-mediated aqueous-phase photoreaction of methoxyphenols - Racliffe Weng Seng Lai; Tian Qiu; Xuyang Zhang; Yalin Wang; Tianwei Hao; Xinlei Ge; Lin Du; Mingjin Tang; Ka In Hoi; Kai Meng Mok; Yong Jie Li (Atmospheric Environment, 2025)

Activation of Peroxymonosulfate by Magnetic MnFe2O4/MWCNT Toward Rhodamine B Degradation: Efficiency, Mechanism and Influencing Factors - Lijia Zheng; Shoutao Cao; Meng Tang; Ming Ge (Water, Air, & Soil Pollution, 2025)

Understanding the factors influencing high-temperature Daqu from different geographical regions - Zhendong Zhang; Yaolan Meng; Yurong Wang; Qiangchuan Hou; Haibo Zhang; Ming Zhang; Ge Hu; Yingying Zhou; Qifu Pan; Zhuang Guo (Food Bioscience, 2024)

CMPK2 Promotes CD4+ T Cell Activation and Apoptosis through Modulation of Mitochondrial Dysfunction in Systemic Lupus Erythematosus - Ya-Nan Tan; Ge-Ge Jiang; Xiang-Wen Meng; Zhi-Yuan Lu; Yan-Ma; Jin Li; Nan-Xiang; Xiao-Ge Sun; Qian Wang; Xue Wang; Xiao-Yi Jia; Min Zhang (Cell Biochemistry and Biophysics, 2024)

A novel macromolecular flame retardant based on sulfonyl diphenol monomer for simultaneous fire safety, transparency and high performance of thin-walled polycarbonate - Zongsheng Liu; Yi Zheng; Bangdong Ge; Meng Ma; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2024)

Dual optimization strategy assisted m-phenylenediamine-based hypercrosslinked polymer loaded ultrafine bimetallic nanoparticles for efficient formic acid dehydrogenation - Hongtan Cai; Qiaoyi Zhang; Xin Liu; Yulin Li; Meiyan Wang; Ge Gao; Zeshuo Meng; Haoteng Sun; Xiufeng Hao (Chemical Engineering Journal, 2024)

Improve the downscaling accuracy of high-resolution precipitation field using classification mask - Ruian Tie; Chunxiang Shi; Meng Li; Xiang Gu; Lingling Ge; Zhanfei Shen; Jieli Liu; Tao Zhou; Xiaojian Chen (Atmospheric Research, 2024)

On the properties of lower mid-latitudes ionospheric scintillation observed over Chengdu, China - Shucan Ge; Hailong Li; Song Zhang; Mengyan Zhu; Jinghua Li; Bin Xu; Tong Xu; Shuji Sun; Lin Meng; Jian Wu (Advances in Space Research, 2024)

The morphological research of ZnxCd1-xS based photocatalysts for energy conversion - Xiuzhen Zheng; Jingbiao Ge; Linfeng Ye; Yang Yang; Jiahui Wang; Wei Ren; Sugang Meng; Shifu Chen (Journal of Environmental Chemical Engineering, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

Comprehensive transcriptomic and metabolomic insights into simultaneous CO2 sequestration and nitrate removal by the Chlorella vulgaris and Pseudomonas sp. consortium - Qian Yu; Xue Chen; Sihan Ai; Xiufeng Wang; Jiayi He; Zhengquan Gao; Chunxiao Meng; Lijun Xi; Baosheng Ge; Fang Huang (Environmental Research, 2024)

Study of the electrospun PVDF fibrous membrane in capturing particulate matters in smoke by the synergy between GO and CNWs - Xiuling Lin; Jieqi Zhang; Ge Meng; Chao Zhang; Chen Yu (Chemical Engineering Journal, 2024)

Promoting adsorption-diffusion-deposition of Zn2+ via a highly reactive modulator for dendrite-free and kinetics-enhanced Zn metal anode - Yilun Ren; Haifeng Bian; Shaozhong Chang; Yujie Ma; Hao Wu; Qing Zhou; Shunshun Jia; Ge Xue; Jian Gu; Haiming Lu; Xiangkang Meng (Chemical Engineering Journal, 2024)

Superior microplastic removal and gravity-driven membrane filtration optimization: The role of octadecyl-quaternium hybrid coagulant and molecular dynamics insights - Meng Chen; Jun Nan; Langrun Song; Wenxing Jin; Shutong Chen; Zhencheng Ge; Fangmin Wu; Xuesong Ye (Chemical Engineering Journal, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Complete Genome Sequence of Candida mucifera from an Otitis Media Patient - Rong-Chen Dai; Jing Guan; Ya-Ting Ning; Timothy Kudinha; Wei Zhang; Xin-Fei Chen; Ge Zhang; Ying-Chun Xu; Meng Xiao (Mycopathologia, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Influence of deep foundation pit excavation on surrounding environment: a case study in Nanjing, China - Chenhe Ge; Meng Yang; Pengfei Li; Mingju Zhang (Acta Geophysica, 2024)

Distributions of nutrients, trace metals, phytoplankton composition, and elemental consumption in the Ross and Amundsen Seas - Yuncong Ge; Ruifeng Zhang; Zhuoyi Zhu; Jun Zhao; Zhu Zhu; Ziang Li; Bingrui Li; Zhaoru Zhang; Yu Zhang; Meng Zhou; Seth John; Walker O. Smith (Marine Chemistry, 2024)

Long-term cover crops boost multi-nutrient cycling and subsurface soil carbon sequestration by alleviating microbial carbon limitation in a subtropical forest - Kai Ding; Liyao Chen; Yuting Zhang; Siyu Ge; Yiman Zhang; Meng Lu; Zhenming Shen; Zaikang Tong; Junhong Zhang (CATENA, 2024)

CircZFR promotes colorectal cancer progression via stabilizing BCLAF1 and regulating the miR-3127-5p/RTKN2 axis - Jiaxin Chen; Huijuan Wang; Jianbin Xu; Engeng Chen; Qing Meng; Jiawei Wang; Haoyi Xiang; Wei Zhou; Ge Shan; Zhenyu Ju; Zhangfa Song (Science China Life Sciences, 2024)

LEO enhanced GNSS (LeGNSS) precise point positioning with emphasis on model comparison - Haibo Ge; Guanlong Meng; Bofeng Li (Advances in Space Research, 2024)

Does climate change increase the risk of marine toxins? Insights from changing seawater conditions - Ruiyang Meng; Xingde Du; Kangfeng Ge; Chunrui Wu; Zongxin Zhang; Xiao Liang; Jun Yang; Huizhen Zhang (Archives of Toxicology, 2024)

Microstructure regulation of Zn0.5Cd0.5S for enhancing the photocatalytic H2 production - Yang Yang; Wei Ren; Jiahui Wang; Xiuzhen Zheng; Jingbiao Ge; Sugang Meng; Shifu Chen; Chun Cai (Fuel, 2024)

A robust and low-cost blended-fiber-based evaporator with high efficiency for solar desalination - Qianqian Liu; Xiangjun Liu; Ge Chen; Pei Feng; Yucheng Xiong; Meng An; Cheng Shao; Xiongfei Zhu; Renzong Wang; Jianshi Sun; Jisheng Sun; Chunfang Guo; et al. (Desalination, 2024)

Conformational interlocking induced construction of hierarchically porous graphene membrane for ultrahigh-pressure sensing - Cong Liu; Hefeng Li; Jikang Zhao; Jiabao Zhu; Xianhua Huan; Yixuan Zhang; Ke Xu; Hongbo Geng; Xiaopeng Chen; Wenhui Ding; Lei Zu; Lei Ge; et al. (Chemical Engineering Journal, 2024)

Coordination-induced amidated modified polyacrylonitrile loaded ultrafine palladium nanoparticles for thermocatalytic hydrogen evolution - Qiaoyi Zhang; Hongtan Cai; Xin Liu; Yulin Li; Meiyan Wang; Ge Gao; Zeshuo Meng; Haoteng Sun; Xiufeng Hao (Chemical Engineering Journal, 2024)

Soil development trajectories, chemical weathering and pedogenic mineral (trans)formation on glauconitic calcarenites in a Mediterranean area - Markus Egli; Meng-Ge Zhang; Michael Plötze; Evdokia Tema; Maziar Mohammadi; Qiu-Bing Wang; Salvatore Raimondi (CATENA, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Regulation of fadR on the ROS defense mechanism in Shewanalla oneidensis - Qiu Meng; Yinming Xu; Liming Dai; Xuzhe Ge; Pei Qiao (Biotechnology Letters, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Nanoplastics induced health risk: Insights into intestinal barrier homeostasis and potential remediation strategy by dietary intervention - Xuemei Meng; Lei Ge; Jiawei Zhang; Jinkai Xue; Graciela Gonzalez-Gil; Johannes S. Vrouwenvelder; Shaomin Guo; Zhenyu Li (Journal of Hazardous Materials, 2024)

Reduction of selenite to selenium nanoparticles by highly selenite-tolerant bacteria isolated from seleniferous soil - Meng Ge; Shaofeng Zhou; Daobo Li; Da Song; Shan Yang; Meiying Xu (Journal of Hazardous Materials, 2024)

The effect and mechanism of combined exposure of MC-LR and NaNO2 on liver lipid metabolism - Jun Yang; Zongxin Zhang; Xingde Du; Yongshui Wang; Ruiyang Meng; Kangfeng Ge; Chunrui Wu; Xiao Liang; Huizhen Zhang; Hongxiang Guo (Environmental Research, 2024)

Long-term cover crop monocultures and mixtures improve soil multifunctionality and shift microbial communities and functions - Kai Ding; Yuting Zhang; Siyu Ge; Yiman Zhang; Meng Lu; Zhenming Shen; Zaikang Tong; Junhong Zhang (European Journal of Agronomy, 2024)

Ablated Sonic Hedgehog Signaling in the Dentate Gyrus of the Dorsal and Ventral Hippocampus Impairs Hippocampal-Dependent Memory Tasks and Emotion in a Rat Model of Depression - Yan Luo; Yan Wang; Feng Qiu; Guanghan Hou; Jian Liu; Hui Yang; Mei Wu; Xuanqi Dong; Dongwei Guo; Ziyan Zhong; Xi Zhang; Jinwen Ge; et al. (Molecular Neurobiology, 2024)

A real-time detection method for GPS flex power - Guanlong Meng; Haibo Ge; Bofeng Li (GPS Solutions, 2024)

Seismic effectiveness evaluation and optimized design of tie up method for securing museum collections - Meng Wang; Yi Yan; Weiguo Yang; Pei Liu; Jiaqi Ge; Botao Ma (Earthquake Engineering and Engineering Vibration, 2024)

Insights into temporal and spatial evolutions of air saturation and its effects on nitrobenzene removal during air sparging remediation - Meng Yao; Xuyang Chen; Min Ge; Peiyuan Xiao; Bowen Li; Mingxin Wang (Journal of Environmental Chemical Engineering, 2024)

Glutamic Acid-Enhanced Phosphate Fertilizer Increases Phosphorus Availability in Fluvo-Aquic Soil via Phosphamide (O = P-N) Formation, Decreasing Phosphate Fixation and Increasing Soil Microbial Diversity - Yingqiang Zhang; Shuiqin Zhang; Bingqiang Zhao; Yanting Li; Meng Xu; Yan’ge Yan; Jianyuan Jing; Liang Yuan (Journal of Soil Science and Plant Nutrition, 2024)

Calcium-based polymers for suppression of soil acidification by improving acid-buffering capacity and inhibiting nitrification - Fei Kang; Yunshan Meng; Yanning Ge; Yun Zhang; Haixiang Gao; Xueqin Ren; Jie Wang; Shuwen Hu (Journal of Environmental Sciences, 2024)

An Underwater Localization Method Based on Visual SLAM for the Near-Bottom Environment - Zonglin Liu; Meng Wang; Hanwen Hu; Tong Ge; Rui Miao (Journal of Marine Science and Engineering, 2024)
The feature matching of the near-bottom visual SLAM is influenced by underwater raised sediments, resulting in tracking loss. In this paper, the novel visual SLAM system is proposed in the underwater raised sediments environment. The underwater images are firstly classified based on the color recognition method by adding the weights of pixel location to reduce the interference of similar colors on the seabed. The improved adaptive median filter method is proposed to filter the classified images by using the mean value of the filter window border as the discriminant condition to retain the original features of the image. The filtered images are finally processed by the tracking module to obtain the trajectory of underwater vehicles and the seafloor maps. The datasets of seamount areas captured in the western Pacific Ocean are processed by the improved visual SLAM system. The keyframes, mapping points, and feature point matching pairs extracted from the improved visual SLAM system are improved by 5.2%, 11.2%, and 4.5% compared with that of the ORB-SLAM3 system, respectively. The improved visual SLAM system has the advantage of robustness to dynamic disturbances, which is of practical application in underwater vehicles operated in near-bottom areas such as seamounts and nodules.

Atom-by-atom optimizing the surface termination of Fe-Pt intermetallic catalysts for alkaline hydrogen evolution reaction - Qing Liang; Fanling Meng; Wenwen Li; Xu Zou; Kexin Song; Xin Ge; Zhou Jiang; Yuhua Liu; Meiqi Liu; Zhenyu Li; Taowen Dong; Zhongjun Chen; et al. (Science Bulletin, 2024)

Positive effects of biochar application and Rhizophagus irregularis inoculation on mycorrhizal colonization, rice seedlings and phosphorus cycling in paddy soils - Yixuan CHEN; Zhonghua WEN; Jun MENG; Zunqi LIU; Jialong WEI; Xiyu LIU; Ziyi GE; Wanning DAI; Li LIN; Wenfu CHEN (Pedosphere, 2024)

Influence of electrochemical descaling treatment in simulated cooling water on the corrosion behavior of stainless steel - Jun Wu; Jinrong Huang; Zhuoran Li; Hua Yang; Honghua Ge; Xinjing Meng; Yuzeng Zhao (Journal of Cleaner Production, 2024)

Biotransformation characteristics of tetracycline by strain Serratia marcescens MSM2304 and its mechanism evaluation based on products analysis and genomics - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yixuan Chen; Jun Meng (Journal of Environmental Management, 2024)

Scattering of mode-1 M2 internal tide in the South China Sea - Wanqian Chen; Bingtian Li; Jinpeng Gao; Xiangqian Meng; Jing Lv; Yunxiu Ge; Yining Wang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

Effects of urban vegetation on microclimate and building energy demand in winter: An evaluation using coupled simulations - Juejun Ge; Yupeng Wang; Dian Zhou; Zhaolin Gu; Xiangzhao Meng (Sustainable Cities and Society, 2024)

Advances in polychlorinated biphenyls-induced female reproductive toxicity - Chunrui Wu; Xingde Du; Haohao Liu; Xinghai Chen; Kangfeng Ge; Ruiyang Meng; Zongxin Zhang; Huizhen Zhang (Science of The Total Environment, 2024)

Micro-macro investigation on bio-cemented sand under different grouting saturation: An effective enhancement method - Ji-Peng Wang; Meng-Chen Li; Meng Qi; Shangqi Ge; Abdelali Dadda (Geomechanics for Energy and the Environment, 2024)

Seismic performance of precast concrete sandwich walls with bolt-steel plate connection - Qi Ge; Yongjie Meng; Jingsong Ai; Wenhao Zuo; Feng Xiong; Ye Liu; Na Dong (Engineering Structures, 2024)

Highly dispersed ultrasmall BiOCl nanoclusters on graphene sheets as high-performance anion-capture electrode for hybrid capacitive deionization - Weiqing Kong; Xu Ge; Desheng Kong; Chenmiao Liu; Jianpeng Sun; Xiao Zhu; Meng Zhang; Yuanyuan Feng (Desalination, 2024)

Visible-light Excited and Highly Photostable Organic Fluorophore with dual-state Emission - Yongchao Li; Liqing Zhang; Xianfeng Meng; Guowei Shi; Wei Gao; Guiyun Duan; Yanqing Ge (Journal of Fluorescence, 2024)

How low-velocity non-Darcian flow in low-permeability media controls the leakage characteristics of a leaky aquifer system - Xianmeng Meng; Ge Yan; Lintao Shen; Maosheng Yin; Dengfeng Liu (Hydrogeology Journal, 2024)

The cytotoxicity of microcystin-LR: ultrastructural and functional damage of cells - Kangfeng Ge; Xingde Du; Haohao Liu; Ruiyang Meng; Chunrui Wu; Zongxin Zhang; Xiao Liang; Jun Yang; Huizhen Zhang (Archives of Toxicology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

How does the digital economy affect the provincial “zero-waste city” construction? Evidence from China - Meng-Ge Hao; Shi-Chun Xu; Xiao-Na Meng; Xiao-Fei Xue (Environmental Science and Pollution Research, 2024)

Effects of soil water content on Cd immobilization and uptake by leek with the combined application of biochar and organic fertilizer - Shuang Huang; Lei Xin; Zhuowen Meng; Haimeng Ge; Zhongbing Lin (Environmental Science and Pollution Research, 2024)

Variations in life history parameters, population dynamics, and transcriptome regulation of Brachionus plicatilis exposed to triclosan - YunhongYang; Tianyue Mao; Yifan Ding; Lingling Ge; Lei Feng; Meng Cai; Cui Han; Jiaxin Yang (Marine Pollution Bulletin, 2024)

Cadmium levels and soil pH drive structure and function differentiation of endophytic bacterial communities in Sedum plumbizincicola: A field study - Jinming Zhang; Meng Na; Yukun Wang; Wen Ge; Jihai Zhou; Shoubiao Zhou (Science of The Total Environment, 2024)

Retrieving hourly seamless PM2.5 concentration across China with physically informed spatiotemporal connection - Yu Ding; Siwei Li; Jia Xing; Xi Li; Xin Ma; Ge Song; Mengfan Teng; Jie Yang; Jiaxin Dong; Shiyao Meng (Remote Sensing of Environment, 2024)

Optimizing groundwater radium end-members in submarine groundwater discharge estimation by incorporating groundwater flow information - Manhua Luo; Mingchen Ge; Xuejing Wang; Wei Wang; Gang Li; Kai Xiao; Zhaoxi Liu; Meng Yao; Hailong Li (Journal of Hydrology, 2024)

Catalytic gasification of anthracene in supercritical water with Ni/TiO2 catalyst: Products distribution and kinetics - Fanrui Meng; Shenghui Guo; Shi Liu; Changyifan Ren; Xingang Qi; Hui Jin; Zhiwei Ge; Liejin Guo (Fuel, 2024)

The Effects of Excipients on Freeze-dried Monoclonal Antibody Formulation Degradation and Sub-Visible Particle Formation during Shaking - Meng-Jia Jin; Xin-Zhe Ge; Qiong Huang; Jia-Wei Liu; Rahul G. Ingle; Dong Gao; Wei-Jie Fang (Pharmaceutical Research, 2024)

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

A graphene@Cu-MOF hybrid synthesized by mechanical ball milling method and its flame retardancy and smoke suppression effect on EP - Ge Zhang; Weihong Wu; Meng Yao; Yumeng Cui; Yunhong Jiao; Hongqiang Qu; Jianzhong Xu (Chemosphere, 2024)

Bearing capacities and failure behaviors of bolt fasten wedge (BFW) active joints used in prestressed internal supports - Mingju Zhang; Chenhe Ge; Pengfei Li; Weizi Wan; Meng Yang (Tunnelling and Underground Space Technology, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Association between combined exposure to dioxins and arthritis among US adults: a cross-sectional study - Qi Meng; Yi Wang; Tao Yuan; Yang Su; Jianxun Ge; Shankun Dong; Shui Sun (Environmental Science and Pollution Research, 2023)

Explaining nitrogen turnover in sediments and water through variations in microbial community composition and potential function - Shan Yang; Meijun Dong; Huibin Lu; Zhipeng Cai; Meng Ge; Jia Xing; Haobin Huang; Youda Huang; Guoping Sun; Shaofeng Zhou; Meiying Xu (Chemosphere, 2023)

Construction of floatable flower-like plasmonic Bi/BiOCl-loaded hollow kapok fiber photocatalyst for efficient degradation of RhB and antibiotics - Yankai Song; Anchun Long; Xianlong Ge; Zongqi Bao; Minfeng Meng; Shaohua Hu; Yingying Gu (Chemosphere, 2023)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

A personalized regression model for predicting thermal sensation based on local skin temperature in moderate summer conditions - Yun Qi; Rui Wang; Chaoyi Zhao; Chao Ding; Chenqiu Du; Jiazheng Zhang; Xuan Zhang; Xinchang Chen; Mingjie Zhang; Qingfeng Bie; Meng Ge (Energy and Buildings, 2023)

Effect of water mist stimulation on dynamic thermal response of pedestrians in summer - Yi Gao; Liming Ge; Tian Zhong; Xi Meng (Building and Environment, 2023)

Spatial distribution and risk assessment of polycyclic aromatic hydrocarbons in soils from contaminated sites in Eastern China - Xinhui Sun; Qi Zhao; Xuelin Li; Qiuyue Zhang; Meng Gao; Zhanpeng Ge; Yu Wang; Hongwen Sun (Environmental Geochemistry and Health, 2023)

A Sedentary Lifestyle Changes the Composition and Predicted Functions of the Gut Bacterial and Fungal Microbiota of Subjects from the Same Company - Longwei Xu; Wenkun Li; Lu Ling; Ziran Zhang; Zilu Cui; Jiang Ge; Yun Wang; Qianlong Meng; Yadan Wang; Kuiliang Liu; Jun Zhou; Fanxin Zeng; et al. (Current Microbiology, 2023)
A sedentary lifestyle affects the diversity and composition of the gut microbiota, but previous studies have mainly focused on bacteria instead of fungi. Here, we compared both the fecal bacterial and fungal microbiota compositions and functions in sedentary persons and controls. Subjects from the China Railway Corporation, including 99 inspectors and 88 officials, were enrolled in our study. Fecal microbiota communities were analyzed using 16S rRNA gene sequencing for bacteria and ITS sequencing for fungi. We found that the diversity of the gut microbiota of the sedentary group was significantly lower than that of the control group ( P < 0.05). The sedentary group had a higher abundance of Firmicutes, a lower abundance of Actinobacteria and Proteobacteria and a higher abundance of Ascomycota, and a lower abundance of Basidiomycota. Furthermore, functional prediction analysis of the fungal microbiota revealed more L-tryptophan degradation to 2-amino-3-carboxymuconate semialdehyde, more phospholipid remodeling (phosphatidylethanolamine, yeast), and more L-tyrosine degradation I, as well as less pentose phosphate pathway (non-oxidative branch), less adenosine nucleotide biosynthesis and less L-valine biosynthesis in the sedentary group ( P < 0.05). Thus, a sedentary lifestyle changes the composition and function of the gut microbiota. It may change the pentose phosphate pathway (non-oxidative branch), nucleic acid and amino acid biosynthesis and phospholipid metabolism in fungi.

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Adsorption characterization of tetracycline antibiotics on alkali-functionalized rice husk biochar and its evaluation on phytotoxicity to seed germination - Siyu Wang; Yixuan Chen; Shaohua Ge; Zunqi Liu; Jun Meng (Environmental Science and Pollution Research, 2023)

Can digital-real integration promote industrial green transformation: Fresh evidence from China's industrial sector - Xiao-Na Meng; Shi-Chun Xu; Meng-Ge Hao (Journal of Cleaner Production, 2023)

Experimental and numerical studies on the interaction between two identical slot jet H2/CO diffusion flames - Huanhuan Xu; Yi Ge; Shouyan Chen; Fanxing Meng; Zilin Zhu; Xiaohan Ren (Fuel, 2023)

A comparative transcriptome analysis of how shrimp endure and adapt to long-term symbiosis with Enterocytozoon hepatopenaei infection - Leiting Zhang; Sheng Zhang; Yi Qiao; Xiaowei Cao; Ge Jiang; Jie Cheng; Xihe Wan; Qingguo Meng; Hui Shen (Fish & Shellfish Immunology, 2023)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Understory vegetation restoration improves soil physicochemical properties, enzymatic activity, and changes diazotrophic communities in Cunninghamia lanceolata plantations but depends on site history - Kai Ding; Yuting Zhang; Anna Yang; Yiman Zhang; Meng Lu; Siyu Ge; Yongbin Qiu; Junhong Zhang; Zaikang Tong (Plant and Soil, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Optimization of ship routing and allocation in a container transport network considering port congestion: A variational inequality model - Lingpeng Meng; Hu Ge; Xudong Wang; Wei Yan; Chuanfeng Han (Ocean & Coastal Management, 2023)

Efficiently elimination of high concentration dye pollutants by Ph-C≡C-Cu/nanoparticles hybrids - Jiawei Hou; Meng Tian; Yadi Bai; Jing Qian; Ya-Ge Liu; Biyun Jing; Yibing Jia; Hai-Ying Jiang (Journal of Water Process Engineering, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

The effects and mechanisms of the new brominated flame retardant BTBPE on thyroid toxicity - Qiong Zhang; Zhenyu Wang; Qianqian Xiao; Jianhong Ge; Xiaoyun Wang; Wanyu Jiang; Yuese Yuan; Yimeng Zhuang; Qinghe Meng; Jianjun Jiang; Weidong Hao; Xuetao Wei (Food and Chemical Toxicology, 2023)

Toward flame-retardant, transparency, and high mechanical property of polycarbonate based on low addition of linear polyborosiloxane - Zongsheng Liu; Meng Ma; Bangdong Ge; Yi Zheng; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2023)

Quinoxaline-based non-fullerene guest acceptor enables ternary organic solar cells achieving 18.9% efficiency via reducing energy loss and regulating morphology - Hui Liu; Zhenyu Chen; Ruixiang Peng; Yi Qiu; Jingyu Shi; Jintao Zhu; Yuanyuan Meng; Ziyan Tang; Jinna Zhang; Fei Chen; Ziyi Ge (Chemical Engineering Journal, 2023)

Dual Förster resonance energy transfer effects enables high photocurrent density and high fill factor in ternary organic solar cells - Hongqian Wang; Daobin Yang; Pengfei Ding; Lin Xie; Zhenyu Chen; Shuncheng Yang; Pengyu Yan; Yuanyuan Meng; Jianqi Zhang; Zhixiang Wei; Ziyi Ge (Chemical Engineering Journal, 2023)

Building energy demand of urban blocks in Xi'an, China: Impacts of high-rises and vertical meteorological pattern - Juejun Ge; Yupeng Wang; Dian Zhou; Zhaolin Gu; Xiangzhao Meng (Building and Environment, 2023)

Deep neural network-estimated age using optical coherence tomography predicts mortality - Ruiye Chen; Shiran Zhang; Guankai Peng; Wei Meng; Grace Borchert; Wei Wang; Zhen Yu; Huan Liao; Zongyuan Ge; Mingguang He; Zhuoting Zhu (GeroScience, 2023)
The concept of biological age has emerged as a measurement that reflects physiological and functional decline with ageing. Here we aimed to develop a deep neural network (DNN) model that predicts biological age from optical coherence tomography (OCT). A total of 84,753 high-quality OCT images from 53,159 individuals in the UK Biobank were included, among which 12,631 3D-OCT images from 8,541 participants without any reported medical conditions at baseline were used to develop an age prediction model. For the remaining 44,618 participants, OCT age gap, the difference between the OCT-predicted age and chronological age, was calculated for each participant. Cox regression models assessed the association between OCT age gap and mortality. The DNN model predicted age with a mean absolute error of 3.27 years and showed a strong correlation of 0.85 with chronological age. After a median follow-up of 11.0 years (IQR 10.9–11.1 years), 2,429 deaths (5.44%) were recorded. For each 5-year increase in OCT age gap, there was an 8% increased mortality risk (hazard ratio [HR] = 1.08, CI:1.02–1.13, P = 0.004). Compared with an OCT age gap within ± 4 years, OCT age gap less than minus 4 years was associated with a 16% decreased mortality risk (HR = 0.84, CI: 0.75–0.94, P = 0.002) and OCT age gap more than 4 years showed an 18% increased risk of death incidence (HR = 1.18, CI: 1.02–1.37, P = 0.026). OCT imaging could serve as an ageing biomarker to predict biological age with high accuracy and the OCT age gap, defined as the difference between the OCT-predicted age and chronological age, can be used as a marker of the risk of mortality.

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Systemic effects of nanoplastics on multi-organ at the environmentally relevant dose: The insights in physiological, histological, and oxidative damages - Xuemei Meng; Lei Ge; Jiawei Zhang; Jinkai Xue; Graciela Gonzalez-Gil; Johannes S. Vrouwenvelder; Zhenyu Li (Science of The Total Environment, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Contrasting effects of nitrogen and phosphorus additions on fine root production and morphological traits of different plant functional types in an ombrotrophic peatland - Leming Ge; Chen Chen; Tong Li; Zhao-Jun Bu; Meng Wang (Plant and Soil, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Decreasing O2 availability reduces cellular protein contents in a marine diatom - Bokun Chen; Hui Song; Xue Yang; Ge Xu; Wei Zhao; Yue Meng; Gang Li (Science of The Total Environment, 2023)

A taphonomic clock based on the coral grain size of beach sediments from the Yongle Atoll, South China Sea - Yali Li; Xinqing Zou; Ming Tan; Chendong Ge; Meng Tang; Teng Wang; Xuefeng Wang (Geomorphology, 2023)

Species identification of culinary spices with two-locus DNA barcoding - Meng-Yue Zhou; Ran-Ran Xing; Ke-Han Liu; Yi-Qiang Ge; Ying Chen (Food Control, 2023)

Inoculation with thermophiles enhanced the food waste bio-drying and complicated interdomain ecological networks between bacterial and fungal communities - Fucheng Teng; Ge Tan; Tianbo Liu; Teng Zhang; Yongjun Liu; Sheng Li; Can Lei; Xing Peng; Huaqun Yin; Delong Meng (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Spatial organization and connectivity of wood rays in Pinus massoniana xylem based on high-resolution μCT-assisted network analysis - Lingyu Ma; Qiulu Meng; Xiaomei Jiang; Zhedong Ge; Zixiong Cao; Yupei Wei; Lichao Jiao; Yafang Yin; Juan Guo (Planta, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Anti-ricin toxin human neutralizing antibodies and DMAbs protection against ricin toxin poisoning - Haotian Yu; Meng Wu; Na Zhao; Mingxin Dong; Yan Wang; Kaikai Yu; Chengbiao Sun; Na Xu; Liangpeng Ge; Wensen Liu (Toxicology Letters, 2023)

Toward a comprehensive understanding of various milling methods on the physicochemical properties of highland barley flours and eating quality of corresponding sugar-free cookies - Fei Ge; Ruhui Xia; Di Wu; Weiwei Cheng; Linghan Meng; Zhenjiong Wang; Xiaozhi Tang (Food Chemistry, 2023)

Aging Effects on the Toxicity Alteration of Different Types of Organic Aerosols: A Review - Ruoyuan Lei; Ziqian Wei; Meijuan Chen; Haifeng Meng; Yun Wu; Xinlei Ge (Current Pollution Reports, 2023)

Magnetic MnFe2O4 nanoparticles anchored on sludge-derived biochar in activating peroxydisulfate for levofloxacin degradation: Mechanism, degradation pathways and cost analysis - Xiaoyan Meng; Tingting Song; Chao Zhang; Huayu Wang; Ming Ge; Changsheng Guo (Journal of Environmental Chemical Engineering, 2023)

The differentiation between condensed and hydrolyzable tannins with different molecular weights in affecting the rheological property of wheat flour-based dough - Wenju Ge; Yan Xu; Meng Niu; Caihua Jia; Siming Zhao (Journal of Cereal Science, 2023)

Poly-p-phenylene as a novel pseudocapacitive anode or cathode material for hybrid capacitive deionization - Weiqing Kong; Xu Ge; Mengqi Yang; Qingao Zhang; Jingyi Lu; Haokun Wen; Hanyu Wen; Desheng Kong; Meng Zhang; Xiao Zhu; Yuanyuan Feng (Desalination, 2023)

The crosstalk between ubiquitination and endocrine therapy - Yidong Ge; Ziqing Zhan; Meng Ye; Xiaofeng Jin (Journal of Molecular Medicine, 2023)

Seeing the forest and the trees: Holistic view of social distancing on the spread of COVID-19 in China - Danlin Yu; Yaojun Zhang; Jun Meng; Xiaoxi Wang; Linfeng He; Meng Jia; Jie Ouyang; Yu Han; Ge Zhang; Yao Lu (Applied Geography, 2023)

Au/SiNCA-based SERS analysis coupled with machine learning for the early-stage diagnosis of cisplatin-induced liver injury - Shengjie Ge; Gaoyang Chen; Dawei Cao; Hechuan Lin; Ziyang Liu; Meng Yu; Shiyi Wang; Zhigang Wang; Ming Zhou (Analytica Chimica Acta, 2023)

Mechanisms underlying the effects of low concentrations of chlorantraniliprole on development and reproduction of the fall armyworm, Spodoptera frugiperda - Jie Yang; Daojie Guan; Jiaping Wei; Huichen Ge; Xiaoli Cao; Susu Lv; Xiaoyang Zhou; Yang Zheng; Xiangkun Meng; Jianjun Wang; Kun Qian (Pesticide Biochemistry and Physiology, 2023)

Effects of molecular structure and existing forms on degradation of emerging contaminants by LaFeO3/NDA−99−oxygen vacancy−driven photo−Fenton system - Xiaodong Ge; Guanhua Meng; Baohe Liu (Journal of Cleaner Production, 2023)

Transcriptomics, metabolomics, antioxidant enzymes activities and respiration rate analysis reveal the molecular responses of rice to Cd stress and/or elevated CO2 concentration - Lanlan Wang; Ge Wang; Jinghui Cui; Xuhao Wang; Meng Li; Xiufen Qi; Xuemei Li; Yueying Li; Lianju Ma (Plant and Soil, 2023)

Study on the dust migration law and a spray dust suppression scheme in transportation roadway - Deji Jing; Mingxing Ma; Shaocheng Ge; Tian Zhang; Xiangxi Meng; Shuaishuai Ren (Environmental Science and Pollution Research, 2023)

Effects of Selenoprotein S Knockdown on Endoplasmic Reticulum Stress in ATDC5 Cells and Gene Expression Profiles in Hypertrophic Chondrocytes - Hui Wang; Zhengzheng Li; Yinan Liu; Meng Zhang; Yawen Shi; Ying Zhang; Ge Mi; Mengying Wang; Ying He; Yonghui Chen; Chen Chen; Jinghong Chen (Biological Trace Element Research, 2023)

Inhibitory effect of volatile organic compounds from Bacillus flexus TR-1 against Aspergillus flavus and aflatoxins in grains during storage - An-Dong Gong; Meng-Ge Song; Hua-Ling Wang; Gao-Zhan Wang; Jian-Hua Wang; Jing-Bo Zhang (BioControl, 2023)

Correction to: Can new energy demonstration city policy reduce carbon emissions? A quasi‑natural experiment from China - Lu Liu; Yuxin Meng; Asif Razzaq; Xiaodong Yang; Wenfeng Ge; Yang Xu; Qiying Ran (Environmental Science and Pollution Research, 2023)

Highly selective electrosynthesis of H2O2 by N, O co-doped graphite nanosheets for efficient electro-Fenton degradation of p-nitrophenol - Fangmin Wu; Jun Nan; Tianzuo Wang; Zhencheng Ge; Bohan Liu; Meng Chen; Xuesong Ye (Journal of Hazardous Materials, 2023)

Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution - Meng-Xuan Li; Bo Xiao; Zi-Yi Zhao; Yu Ma; Ya-Nan Zhou; Xin-Yu Zhang; Feng-Ge Wang; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Influence mechanism of ammonia mixing on NO formation characteristics of pulverized coal combustion and N oxidation in ammonia-N/coal-N - Ping Chen; Changhao Hua; Boyu Jiang; Mingyan Gu; Zhenling Ge; Meng Zhang; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

Cooling energy saving by vegetation planting in high-density districts: Evaluation using the coupled simulation - Juejun Ge; Yupeng Wang; Hashem Akbari; Dian Zhou; Zhaolin Gu; Xiangzhao Meng (Building and Environment, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Can new energy demonstration city policy reduce carbon emissions? A quasi-natural experiment from China - Lu Liu; Yuxin Meng; Asif Razzaq; Xiaodong Yang; Wenfeng Ge; Yang Xu; Qiying Ran (Environmental Science and Pollution Research, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Maternal cerium nitrate exposure induces developmental immunotoxicity in BALB/c mouse offspring - Jianhong Ge; Xiaoyun Wang; Qinghe Meng; Mengmeng Tang; Wanyu Jiang; Jianjun Jiang; Qianqian Xiao; Weidong Hao; Xuetao Wei (Toxicology Letters, 2023)

Coumaronochromones, flavanones, and isoflavones from the twigs and leaves of Erythrina subumbrans inhibit PTP1B and nitric oxide production - Cai-Ying Liu; Pan Deng; Bin Wang; Ai-Hong Liu; Meng-Ge Wang; Song-Wei Li; Li-Li Chen; Shui-Chun Mao (Phytochemistry, 2023)

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Efficient degradation of antibiotics by oxygen vacancy-LaFeO3/polystyrene-driven photo-Fenton system: Highlight the impacts of molecular structures - Xiaodong Ge; Guanhua Meng; Baohe Liu (Journal of Water Process Engineering, 2023)

Quantitative partitioning of temporal origin of transpiration into pre- and post-plantation under deep-rooted vegetation on the Loess Plateau of China - Guangjie Chen; Wenjie Wu; Tingfang Meng; Mingyi Wen; Bingcheng Si; Jianqiang He; Min Li; Qin'ge Dong; Hao Feng; Kadambot H.M. Siddique (Journal of Hydrology, 2023)

Perspective: Blinded by the bright—afforestation is affecting widespread sampling deficiency in plant collections - Yu Zhang; Meng-Ge Duan; Pei-Han Huang; Min Li; Hong-Hu Meng; Hui-Jie Qiao; Jie Li (Forest Ecology and Management, 2023)

A cobalt-based forward osmosis draw solute synthesized from lithium-ion battery wastes for cobalt-containing wastewater purification - Rongzhen Chen; Fengrong Qiu; Qing-Wei Meng; Tai-Shung Chung; Qingchun Ge (Desalination, 2023)

Dual metal-organic frameworks-derived Fe-atomic sites bounded to fine Fe/Fe C nanoparticles for enhanced oxygen electroreduction - Meixin Chen; Fantao Kong; Heliang Yao; Yafeng Chen; Ge Meng; Ziwei Chang; Chang Chen; Han Tian; Lianzhou Wang; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2023)

The urgent need to develop a new grassland map in China: based on the consistency and accuracy of ten land cover products - Mengjing Hou; Jing Ge; Yangjing Xiu; Baoping Meng; Jie Liu; Qisheng Feng; Tiangang Liang (Science China Life Sciences, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Design strategies of perovskite nanofibers electrocatalysts for water splitting: A mini review - Yaobin Wang; Yan Jiang; Yunxia Zhao; Xinlei Ge; Qian Lu; Ting Zhang; Dongsheng Xie; Meng Li; Yunfei Bu (Chemical Engineering Journal, 2023)

Identification and genetic characterization of Blastocystis subtypes in Père David's deer (Elaphurus davidianus) from Shishou, China - Fuzhen Ni; Fuchang Yu; Xuefeng Yang; Zhixing An; Yaming Ge; Xuehan Liu; Meng Qi (Veterinary Research Communications, 2023)

Metabolomics and transcriptomics provide insights into the flavonoid biosynthesis pathway in the roots of developing Aster tataricus - Kaixuan Jia; Xiaoling Zhang; Yijiang Meng; Shuqi Liu; Xiaoqing Liu; Taixin Yang; Chunxiu Wen; Lingdi Liu; Shujun Ge (Journal of Plant Research, 2023)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Double knock-in pig models with elements of binary Tet-On and phiC31 integrase systems for controllable and switchable gene expression - Qin Jin; Xiaoyu Yang; Shixue Gou; Xiaoyi Liu; Zhenpeng Zhuang; Yanhui Liang; Hui Shi; Jiayuan Huang; Han Wu; Yu Zhao; Zhen Ouyang; Quanjun Zhang; et al. (Science China Life Sciences, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Facile synthesis of magnetic ZnFe2O4/AC composite to activate peroxydisulfate for dye degradation under visible light irradiation - Tingting Song; Quanbao He; Xiaoyan Meng; Zhangxing He; Ming Ge (Environmental Science and Pollution Research, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

Hydrochemical characteristics and identification of pollution ions of the springs in the south of Yanbian City, China - Fanao Meng; Xiujuan Liang; Changlai Xiao; Ge Wang (Environmental Geochemistry and Health, 2022)

Research on the exploitation and utilization degree of mineral water based on ecological base flow in the Changbai Mountain basalt area, northeast China - Ge Wang; Changlai Xiao; Zhiwei Qi; Qiaofeng Lai; Fanao Meng; Xiujuan Liang (Environmental Geochemistry and Health, 2022)

A Method for Identifying the Key Performance Shaping Factors to Prevent Human Errors during Oil Tanker Offloading Work - Renyou Zhang; Huixing Meng; Jun Ge; Henry Tan (Journal of Marine Science and Engineering, 2022)
Oil tanker offloading is a human-related and high-risk task. A small operational error may trigger catastrophic accidents such as fire and explosion. It is recognised that more than 70% of industrial accidents are blamed for human errors, so preventing them is crucial. As human error is associated with a variety of Performance Shaping Factors (PSFs), it is meaningful to identify key PSFs for safe operations during oil tanker offloading process. However, some issues are obstacles to finding the crucial PSFs. The recording data of most PSFs are always incomplete and imperfect. Moreover, the standard for ranking PSFs should be rational. In addition, the performance of each PSF at the different stages is oil offloading is usually unstable and may change with time. As a result, this study aims to conduct a method that mainly relies on Grey Relational Analysis (GRA), the definition of “Risk” (combination of likelihood and impact), and Hierarchical Task Analysis (HTA) to find several significant PSFs to prevent human errors. GRA deals with the incomplete and imperfect data; the definition of “Risk” provides a rational basis for ranking PSFs; and HTA gives support for considering the PSFs’ changes at different stages of a task. The proposed approach is tested on a real engineering case of oil tanker offloading work at offshore terminal. The result indicates that the method can be applied to identify key PSFs, which in turn provides recommendations for human error prevention to ensure the safety both on board and at terminal.

Mapping and characterization of the Rx3 gene for resistance to Xanthomonas euvesicatoria pv. euvesicatoria race T1 in tomato - Ge Meng; Yao Xiao; Aitong Li; Zilin Qian; Yinge Xie; Luyao Yang; Huabing Lin; Wencai Yang (Theoretical and Applied Genetics, 2022)

Closing the loop of DBS using the beta oscillations in cortex - Chen Liu; Ge Zhao; Zihan Meng; Changsong Zhou; Xiaodong Zhu; Wei Zhang; Jiang Wang; Huiyan Li; Hao Wu; Chris Fietkiewicz; Kenneth A. Loparo (Cognitive Neurodynamics, 2021)

Is Doppler Echocardiography Adequate for Surgical Planning of Single Ventricle Patients? - Zhenglun Alan Wei; Biao Si; Xiaoqian Ge; Meng Zhu; Maria A. Cetatoiu; Chenze Tian; Lixin Sun; Bin Qiao (Cardiovascular Engineering and Technology, 2021)

Retraction Note to: Sensitivity of mountain landslide based on Markov model and aerobic training management - Quan Zhao; Ge Liu; Jiawei Meng (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Sensitivity of mountain landslide based on Markov model and aerobic training management - Quan Zhao; Ge Liu; Jiawei Meng (Arabian Journal of Geosciences, 2021)

Effects of different types of land-use on taxonomic and functional diversity of benthic macroinvertebrates in a subtropical river network - Zhenyuan Liu; Zhengfei Li; Diego M. P. Castro; Xiang Tan; Xiaoming Jiang; Xingliang Meng; Yihao Ge; Zhicai Xie (Environmental Science and Pollution Research, 2021)

The drivers of multiple dimensions of stream macroinvertebrate beta diversity across a large montane landscape - Zhengfei Li; Jani Heino; Zhenyuan Liu; Xingliang Meng; Xiao Chen; Yihao Ge; Zhicai Xie (Limnology and Oceanography, 2021)
Environmental filtering and spatial processes have been associated with variation in ecological communities and biodiversity; however, their relative importance on multiple dimensions of beta diversity has not been fully explored in montane streams. Here, we examined the relative contribution of local, catchment and climate environmental variables and spatial factors to variation in three dimensions of macroinvertebrate beta diversity in the upper Han River Basin. Taxonomic, functional, and phylogenetic beta diversities and their respective turnover and nestedness components were calculated for macroinvertebrate assemblages sampled in a total of 130 stream sites across a large mountainous landscape. We investigated the correlations between beta diversity facets using MSR‐Mantel procedure and then examined the relative influence of each set of ecological factors through redundancy analysis and variance partitioning. Our results revealed relatively low spatial congruence among beta diversity dimensions, indicating these diversity dimensions are independent measures which offer complementary information of community assembly. Beta diversity dimensions and components were best explained by spatial and local environmental factors, whereas the large‐scale catchment and climate factors appeared less influential. Moreover, spatial and environmental factors generally exerted different controls on beta diversity depending on the dimensions under consideration. Taxonomic and phylogenetic beta diversities were more strongly determined by spatial factors via dispersal limitation, while functional beta diversity was mainly associated to local environments through habitat filtering. Our results challenge the perspective that using one diversity facet as a surrogate for others is enough, and highlight the need to integrate multiple diversity dimensions in metacommunity and biodiversity research.

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Comparison of proteome alterations during aging in the temporal lobe of humans and rhesus macaques - Xia Wang; Kang Chen; Meng Pan; Wei Ge; Zhanlong He (Experimental Brain Research, 2020)

Increasing plant diversity offsets the influence of coarse sand on ecosystem services in microcosms of constructed wetlands - Yuanyuan Du; Bin Luo; Wenjuan Han; Yingyao Duan; Chenchen Yu; Meng Wang; Ying Ge; Jie Chang (Environmental Science and Pollution Research, 2020)

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Hanxiong Song; Jingjing Huang; Leming Ge; Changhui Peng; Pengxiang Zhao; Xinyi Guo; Tong Li; Xiaojuan Shen; Qiuan Zhu; Weiguo Liu; Hua Wei; Meng Wang (Plant and Soil, 2020)

Comparative Metabolomic and Transcriptome Analysis Reveal Distinct Flavonoid Biosynthesis Regulation Between Petals of White and Purple Phalaenopsis amabilis - Xiaoqing Meng; Ge Li; Lingya Gu; Yu Sun; Zongyun Li; Jingran Liu; Xiaoqing Wu; Tingting Dong; Mingku Zhu (Journal of Plant Growth Regulation, 2020)

The characteristics of oestrone mobility in water and soil by the addition of Ca-biochar and Fe–Mn-biochar derived from Litchi chinensis Sonn. - Huan-yu Tao; Hui Ge; Jianghong Shi; Xiaowei Liu; Wei Guo; Mengtao Zhang; Yaobin Meng; Xiao-yan Li (Environmental Geochemistry and Health, 2020)

Responses of soil moisture to regional climate change over the Three Rivers Source Region on the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Zhaoguo Li; Yaqiong Lyv; Huajin Lei; Lin Zhao; Shengnan Zhao; Jun Ge; Hui Jing (International Journal of Climatology, 2020)
In this study, soil moisture data from two reanalysis datasets (ERA‐Interim, ERA5), a satellite soil moisture product from the European Space Agency (ESA) and three assimilation datasets from the Global Land Data Assimilation System (GLDAS), that is, GLADS‐NOAH025, GLADS‐NOAH10, and GLDAS‐CLM were compared with the observed soil moisture data in Maqu and Maduo stations over the Three Rivers Source Region (TRSR) on the Tibetan Plateau in China. Comparative statistical parameters between the soil moisture observations and the products, including the root mean square error, correlation coefficient ( R ), and standard deviation ratio were calculated to evaluate the products in different seasons. It was found that most products overestimated the soil moisture values, among which GLADS‐NOAH025 had relatively good consistency with the observations in the surface soil layer (0–10 cm), whereas GLDAS‐CLM agreed well with the observations in the 10–40 cm layer. Both ERA5 and ERA‐interim soil moisture overestimated soil moisture at all levels. The responses of soil moisture to regional climate change over the TRSR were also investigated by using the GLDAS‐NOAH025 soil moisture product, the ESA soil moisture product, and the observations during the nonfreezing period. The results show that the trends of soil moisture are consistent with the precipitation changes in the main central part of the TRSR. A significant positive correlation was found between soil moisture and precipitation in most regions of the TRSR, which indicates that soil moisture increases with the increase of precipitation, except in the northwest TRSR, where the variation of soil moisture was possibly influenced by both the precipitation changes and the increase of evapotranspiration.

Counting Kmers for Biological Sequences at Large Scale - Jianqiu Ge; Jintao Meng; Ning Guo; Yanjie Wei; Pavan Balaji; Shengzhong Feng (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

The distributions, contamination status, and health risk assessments of mercury and arsenic in the soils from the Yellow River Delta of China - Meng Ge; Guijian Liu; Houqi Liu; Zijiao Yuan; Yuan Liu (Environmental Science and Pollution Research, 2019)

Complete mitochondrial genome characterization of the alligator pipefish Syngnathoides biaculeatus and phylogenetic analysis of family Syngnathidae - Lingyan Zhu; Meng Chen; Rubin Cheng; Weihong Ge; Guangji Zhang; Yuqing Ge (Conservation Genetics Resources, 2019)

Relationship between phenotype and genotype of 102 Chinese newborns with Prader–Willi syndrome - Meng-Meng Ge; Yan-Yan Gao; Bing-Bing Wu; Kai Yan; Qian Qin; HuiJun Wang; WenHao Zhou; Lin Yang (Molecular Biology Reports, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Long-term observation of cyanobacteria blooms using multi-source satellite images: a case study on a cloudy and rainy lake - Meng Mu; Chuanqing Wu; Yunmei Li; Heng Lyu; Shengzhong Fang; Xiang Yan; Ge Liu; Zhubin Zheng; Chenggong Du; Shun Bi (Environmental Science and Pollution Research, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Novel biallelic PCNT deletion causing microcephalic osteodysplastic primordial dwarfism type II with congenital heart defect - Lanlan Meng; Chaofeng Tu; Guangxiu Lu; Ge Lin; Yueqiu Tan (Science China Life Sciences, 2019)

The complete mitochondrial genome of the short snouted seahorse Hippocampus hippocampus Linnaeus 1758 (Syngnathiformes: Syngnathidae) and its phylogenetic implications - Meng Chen; Lingyan Zhu; Jianzhen Chen; Guangji Zhang; Rubin Cheng; Yuqing Ge (Conservation Genetics Resources, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) reduction by granular zero-valent iron in continuous flow reactor - Amalia Terracciano; Jie Ge; Agamemnon Koutsospyros; Xiaoguang Meng; Benjamin Smolinski; Per Arienti (Environmental Science and Pollution Research, 2018)

Arsenic removal from water by metal-organic framework MIL-88A microrods - Hao Wu; Meng-Dan Ma; Wei-Zhuo Gai; Hongxun Yang; Jian-Ge Zhou; Zhenxiang Cheng; Pingguang Xu; Zhen-Yan Deng (Environmental Science and Pollution Research, 2018)

Complete mitochondrial genome sequence for the endangered Knysna seahorse Hippocampus capensis Boulenger 1900 - Yuqing Ge; Lingyan Zhu; Meng Chen; Guangji Zhang; Zhen Huang; Rubin Cheng (Conservation Genetics Resources, 2018)

Identification, expression analysis, and function evaluation of 42 tomato DEAD-box RNA helicase genes in growth development and stress response - Jing Cai; Xiaoqing Meng; Ge Li; Tingting Dong; Jian Sun; Tao Xu; Zongyun Li; Yonghua Han; Mingku Zhu (Acta Physiologiae Plantarum, 2018)

Transcriptome Analysis Reveals the Mechanism of Fungicidal of Thymol Against Fusarium oxysporum f. sp. niveum - Meng Zhang; Jing Ge; Xiangyang Yu (Current Microbiology, 2018)

Roles of Nitric Oxide Synthase Isoforms in Neurogenesis - Cheong-Meng Chong; Nana Ai; Minjing Ke; Yuan Tan; Zhijian Huang; Yong Li; Jia-Hong Lu; Wei Ge; Huanxing Su (Molecular Neurobiology, 2018)

Tempo-spatial dynamics of water quality and its response to river flow in estuary of Taihu Lake based on GOCI imagery - Chenggong Du; Yunmei Li; Qiao Wang; Ge Liu; Zhubin Zheng; Meng Mu; Yuan Li (Environmental Science and Pollution Research, 2017)

A rapid and efficient Agrobacterium-mediated transient gene expression system for strawberry leaves and the study of disease resistance proteins - Meng-Yuan Cui; Wei Wei; Kuan Gao; Yin-Ge Xie; Ye Guo; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

First isolation and genetic characteristics of porcine sapeloviruses in Hunan, China - Taotao Yang; Runcheng Li; Wang Peng; Meng Ge; Binyu Luo; Tailong Qu; Xinglong Yu (Archives of Virology, 2017)

Flavonol glycosides from the leaves of Elaeagnus pungens - Ying-ying Shang; Qin Qin; Meng-Shun Li; Hai-yan Xu; Yue-bin Ge (Natural Product Research, 2017)

Characterization of a vacuolar H+-ATPase G subunit gene from Juglans regia (JrVHAG1) involved in mannitol-induced osmotic stress tolerance - Zhenggang Xu; Yunlin Zhao; Yu Ge; Jiao Peng; Meng Dong; Guiyan Yang (Plant Cell Reports, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Expression of inflammation-related genes in the lung of BALB/c mice response to H7N9 influenza A virus with different pathogenicity - Meng Yu; Qingnan Wang; Wenbao Qi; Kaizhao Zhang; Jianxin Liu; Pan Tao; Shikun Ge; Ming Liao; Zhangyong Ning (Medical Microbiology and Immunology, 2016)

Expression Profile and Tissue-Specific Distribution of the Receptor-Interacting Protein 3 in BALB/c Mice - Qingnan Wang; Meng Yu; Kaizhao Zhang; Jianxin Liu; Pan Tao; Shikun Ge; Zhangyong Ning (Biochemical Genetics, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A afferent fibers are involved in the pathology of central changes in the spinal dorsal horn associated with myofascial trigger spots in rats - Fei Meng; Hong-You Ge; Yong-Hui Wang; Shou-Wei Yue (Experimental Brain Research, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

The Effect of Continuous Blood Purification on the Prognosis of Cardiorenal Syndrome Patients - Fengyu Jia; Peng Rong; Dandan Li; Suxia Wang; Ying Jing; Yanming Ge; Jianzhong Meng (Cell Biochemistry and Biophysics, 2015)

Vulnerability assessment of the coastal mangrove ecosystems in Guangxi, China, to sea-level rise - Shasha Li; Xianwei Meng; Zhenming Ge; Liquan Zhang (Regional Environmental Change, 2015)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Terbium promotes adhesion and osteogenic differentiation of mesenchymal stem cells via activation of the Smad-dependent TGF-β/BMP signaling pathway - Dan-Dan Liu; Kun Ge; Yi Jin; Jing Sun; Shu-Xiang Wang; Meng-Su Yang; Jin-Chao Zhang (JBIC Journal of Biological Inorganic Chemistry, 2014)

Genistein Alleviates Radiation-Induced Pneumonitis by Depressing Ape1/Ref-1 Expression to Down-regulate Inflammatory Cytokines - Guo-Dong Liu; Lei Xia; Jian-Wu Zhu; Shan Ou; Meng-Xia Li; Yong He; Wei Luo; Juan Li; Qian Zhou; Xue-Qin Yang; Jin-Lu Shan; Ge Wang; et al. (Cell Biochemistry and Biophysics, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

A New Pyrazoline-Based Fluorescent Probe for Cu2+ in Live Cells - Meng-Meng Li; Shu-Ya Huang; Hui Ye; Fei Ge; Jun-Ying Miao; Bao-Xiang Zhao (Journal of Fluorescence, 2013)

Age assignment and geological significance of the “Budate Group” in the Hailar Basin - Qi’An Meng; ChuanBiao Wan; DeFeng Zhu; YanLong Zhang; WenChun Ge; FuYuan Wu (Science China Earth Sciences, 2013)

Doubled haploids of novel trigenomic Brassica derived from various interspecific crosses - X. X. Geng; S. Chen; I. A. Astarini; G. J. Yan; E. Tian; J. Meng; Z. Y. Li; X. H. Ge; M. N. Nelson; A. S. Mason; A. Pradhan; W. J. Zhou; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Selection and validation of suitable reference genes for mRNA qRT-PCR analysis using somatic embryogenic cultures, floral and vegetative tissues in citrus - Zheng Liu; Xiao-Xia Ge; Xiao-Meng Wu; Shu-Jun Kou; Li-Jun Chai; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Transcriptional profiling of genes involved in embryogenic, non-embryogenic calluses and somatic embryogenesis of Valencia sweet orange by SSH-based microarray - Xiao-Xia Ge; Li-Jun Chai; Zheng Liu; Xiao-Meng Wu; Xiu-Xin Deng; Wen-Wu Guo (Planta, 2012)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein - Ren-Jie Zhou; Xue-Qin Yang; Dong Wang; Qian Zhou; Lei Xia; Meng-Xia Li; Lin-Li Zeng; Ge Wang; Zhen-Zhou Yang (Cell Biochemistry and Biophysics, 2012)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

Nm23-H1 Protein Binds to APE1 at AP Sites and Stimulates AP Endonuclease Activity Following Ionizing Radiation of the Human Lung Cancer A549 Cells - Zhi-Min Zhang; Xue-Qin Yang; Dong Wang; Ge Wang; Zhen-Zhou Yang; Yi Qing; Zhi-Xiang Yang; Meng-Xia Li; De-Bing Xiang (Cell Biochemistry and Biophysics, 2011)

Caspase- and p38-MAPK-dependent induction of apoptosis in A549 lung cancer cells by Newcastle disease virus - Jianchun Bian; Kai Wang; Xiangang Kong; Huairan Liu; Fei Chen; Maozhi Hu; Xiaorong Zhang; Xinan Jiao; Baoxue Ge; Yantao Wu; Songshu Meng (Archives of Virology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Leaf respiration/photosynthesis relationship and variation: an investigation of 39 woody and herbaceous species in east subtropical China - Ziyan Chu; Yijun Lu; Jie Chang; Meng Wang; Hong Jiang; Jinsheng He; Changhui Peng; Ying Ge (Trees, 2011)

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b - Zhi-Bang Deng; Nai-Dong Wang; Dao-Jun Xu; An-Wen Yuan; Meng Ge; Wei Luo; Li-Qun Xue; Xing-Long Yu (Veterinary Research Communications, 2011)

Stage and tissue-specific modulation of ten conserved miRNAs and their targets during somatic embryogenesis of Valencia sweet orange - Xiao-Meng Wu; Mei-Ya Liu; Xiao-Xia Ge; Qiang Xu; Wen-Wu Guo (Planta, 2011)

A novel membrane based process to isolate photosystem-I membrane complex from spinach - Jianguo Liu; Mengmeng Yin; Meng Wang; Xuefang Zhang; Baosheng Ge; Shuang Liu; Jianren Lu; Zhanfeng Cui (Photosynthesis Research, 2011)

Conjugates of folic acids with BSA-coated quantum dots for cancer cell targeting and imaging by single-photon and two-photon excitation - He Meng; Ji-Yao Chen; Lan Mi; Pei-Nan Wang; Mei-Ying Ge; Yang Yue; Ning Dai (JBIC Journal of Biological Inorganic Chemistry, 2011)

Rapid re-convergences to ambiguity-fixed solutions in precise point positioning - Jianghui Geng; Xiaolin Meng; Alan H. Dodson; Maorong Ge; Felix N. Teferle (Journal of Geodesy, 2010)

Characterization of ten microsatellite loci for the dark pomfret, Pampus cinereus (Stromateidae, Perciformes) - Li Wei; Jianxin Wang; Fanxing Meng; Ge Shi; Rixin Wang (Conservation Genetics Resources, 2009)

Different responses of two Mosla species to potassium limitation in relation to acid rain deposition - Meng Wang; Bao-jing Gu; Ying Ge; Zhen Liu; De-an Jiang; Scott X. Chang; Jie Chang (Journal of Zhejiang University-SCIENCE B, 2009)

The contribution of proline residues to protein stability is associated with isomerization equilibrium in both unfolded and folded states - Meng Ge; Xian-Ming Pan (Extremophiles, 2009)

Refolding of the hyperthermophilic protein Ssh10b involves a kinetic dimeric intermediate - Meng Ge; Yong-Jin Mao; Xian-Ming Pan (Extremophiles, 2009)